2004
DOI: 10.3168/jds.s0022-0302(04)73223-3
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: Formation of Keratins in the Bovine Claw: Roles of Hormones, Minerals, and Vitamins in Functional Claw Integrity

Abstract: Keratins are the characteristic structural proteins of the highly cornified epidermis of the skin, feathers, and hoof. Keratin proteins provide the structural basis for the unique properties of the biomaterial horn and its protective function against a wide range of environmental factors. Hoof horn is produced through a complex process of differentiation (keratinization) of epidermal cells. Formation and biochemical binding of keratin proteins and synthesis and exocytosis of intercellular cementing substance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
156
3
26

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(194 citation statements)
references
References 37 publications
4
156
3
26
Order By: Relevance
“…Copper is a vital component of keratin, and deficiency may lead to abnormal sulfur cross-linking, resulting in defective hoof keratin, but generally also defective antlers and hair coat (Gogan et al 1989;Johnson et al 2007), which was not identified in this study or in affected elk in this region in general. Copper deficiency in cattle is associated with increased incidence of infectious hoof disease, heel cracks, and sole ulcers thought to be due to weak, fragile hoof and sole keratin (Tomlinson et al 2004). A population of Alaskan moose was described with lameness and severe overgrowth of the hooves (Flynn et al 1977), and the cause of this lesion, called ''slipper foot,'' was speculated to be copper deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Copper is a vital component of keratin, and deficiency may lead to abnormal sulfur cross-linking, resulting in defective hoof keratin, but generally also defective antlers and hair coat (Gogan et al 1989;Johnson et al 2007), which was not identified in this study or in affected elk in this region in general. Copper deficiency in cattle is associated with increased incidence of infectious hoof disease, heel cracks, and sole ulcers thought to be due to weak, fragile hoof and sole keratin (Tomlinson et al 2004). A population of Alaskan moose was described with lameness and severe overgrowth of the hooves (Flynn et al 1977), and the cause of this lesion, called ''slipper foot,'' was speculated to be copper deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The dermis is responsible for providing the nutrients which are required for the epidermal keratinization process. In the absence of an appropriate blood supply, a low quality corneum tissue is formed increasing the susceptibility of the animal to chemical, physical or biological damages to the environment (Tomlinson et al 2004). In addition, dermal fibroblasts play a modulating role in the keratinocyte growth.…”
Section: Discussionmentioning
confidence: 99%
“…8a and b): stratum basale, stratum spinosum, stratum granulosum and stratum corneum. Cells in the first three layers are differentiating keratinocytes while the outermost stratum corneum is composed of dead keratin-filled corneocytes [81]. The stratum basale is about one cell thick and rests on the basement membrane (BM in Fig.…”
Section: Formation Of Keratinous Materialsmentioning
confidence: 99%
“…Keratinous materials are formed by intracellularly synthesized keratins [81] through epidermal cells which build up at the outermost layer of skin. Keratinization replaces the cytoplasmic content by filamentous proteins, and is part of the cellular differentiation that transforms living and functional cells into cornified, structurally stable dead cells [82,83].…”
Section: Formation Of Keratinous Materialsmentioning
confidence: 99%